Effects of 4° misoriented sapphire substrate on optical property of green InGaN/GaN multiple quantum wells. (January 2018) - Peng, Ruoshi; Bai, Junchun; Xu, Shengrui; Zhang, Jincheng; Du, Jinjuan; Zhao, Ying; Fan, Xiaomeng; Wu, Mei; Hao, Yue
Abstract: The effects of 4° misoriented sapphire substrate on optical property of green InGaN/GaN multiple quantum wells (MQWs) grown on planar c -plane sapphire and vicinal cut sapphire substrates were investigated. About an order of magnitude higher photoluminescent intensity of MQWs on vicinal substrate was observed compared to that of MQWs on planar substrate. Atomic force microscope and scanning electron microscope found there was a large number of V-shape pits on the structure grown on vicinal substrate. Result of Raman demonstrated that there was more stress in MQWs structure on planar substrate. It was identified by high-resolution X-ray diffraction and transmission electron microscope that the structure on vicinal substrate had higher crystalline quality. V-shape MQWs grown on semipolar sidewalls of V-shape pits on vicinal substrate played an important role in improving luminescent intensity. Highlights: Green InGaN/GaN MQWs grown on planar c -plane and vicinal sapphire substrates are investigated. Optical property, surface morphology and crystalline quality of green InGaN/GaN MQWs are investigated. About an order of magnitude higher PL intensity of MQWs on vicinal substrate than on planar substrate is observed. V-shape MQWs grown on the semipolar 10–11 sidewalls of V-shape pits greatly enlarge the total area of MQWs.